A study of clinical profile of cardiac dysfunction in patients with HIV infection - K. K., Sarosh Kumar; B., Jayakumar; R., Baiju (International Journal of Research in Medical Sciences, 2016)
Background: HIV infection is a major health problem across the entire world including India. The introduction of anti-retroviral therapy (ART) have led to a significant reduction in opportunistic infections and hence increased life expectancy of HIV-infected individuals. This resulted in an increase in prevalence of cardiovascular diseases among these individuals. Aim was to study the clinical profile of cardiac dysfunction in patients with HIV infection and to find whether CD-4 influence on the disease pattern and severity. Methods: This study was a cross sectional study conducted in Sixty HIV infected patients who attended Anti-Retroviral Therapy Centre, Government Medical College, Thiruvananthapuram, Kerala, India during a period of fifteen months. Patients underwent a thorough clinical examination and other relevant investigations including CD-4 count, ECG and transthoracic echocardiography. Results: In our study it was found that cardiac involvement is common even in asymptomatic HIV infected patients. Cardiac manifestations observed were left ventricular diastolic dysfunction (25%), left ventricular hypertrophy (15%), dilated cardiomyopathy (15%), pericardial effusion (13.3%) and mild pulmonary artery hypertension (10%). Cardiac involvement is more common in those with low CD-4 count. Among these conditions Concentric Left Ventricular Hypertrophy had a statistically significant correlation with CD-4 count. Conclusions: We observed that some form of cardiac involvement was common even in asymptomatic HIV infected patients and cardiac involvement was inversely associated with CD-4 Count of the patient. Transthoracic echocardiography is a good non-invasive tool for the early detection of cardiac abnormalities. Cardiac involvement can be easily overlooked in these patients as symptoms can be attributed to associated co morbid illnesses, so every HIV infected patients should undergo a thorough clinical examination and relevant cardiac evaluation at the time of diagnosis and periodically to decrease cardiac associated morbidity and mortality.